The “new” pedagogical approach: the skills - Tacca Huamán, Daniel Rubén (2014)
The approach based on skills is relatively new in our context but it has been used in business since 1940. This article shows the different conceptions about skills throughout history, their way from the labor sector to the educational one as a possible definition when one is working on the curricula. Competence; skills; capacities; performance; success